Apoyo emocional de la enfermera y percepción del paciente en pre operatorio. Hospital Regional Docente de Trujillo - 2009 - Bustamante Navío, Ángeles María (2009)
The present study was made in order to establish the relationship between the emotional support of the nurse and the perception of the patient in pre-operation period in the service of “A” surgery of the Docente Regional Hospital of Trujillo, among the months of August 2009 – December 2009. It is a descriptive – correlational research. The sampling universe was formed by 6 nurses and by 51 adult patients who were programmed for surgery in the elective method, having into account that both populations in the study met with the inclusion criteria. The data collection was obtained through applying of the following instruments: “emotional support of the nurse to the patient in pre-operation period” and “perception of the emotional support of the patient in pre-operation period”. Both instruments were filled anonymously with free participation and confidentiality. Once the information was obtained, the data were in layouts and presented in graphics and statistical tables of one and two entries in a numerical and percentage way; in order to measure the association of the variables the Spearman’s rank correlation coefficient was applied. The respective test of statistical significance was also applied (T of Student). For the statistical analysis the test of independence of criteria chi-square test (X2) considered significant (p<0.05); from the analysis and discussion of the results we came to the conclusion that: There is a significant statistical relationship (p=0.019) finding that the 79.4 percent who considered the emotional support the nurse brings as favorable corresponds to a satisfactory perception. The 52.9 percent of the patients in preoperation period affirm that the perception of the emotional support is not satisfactory; it is related to the unfavorable emotional support the nurse brings.